Dampak Promo Go-Food pada Motivasi Pengambilan Keputusan Mahasiswa dalam Perilaku Konsumtif - Fibrianto, Alan Sigit (Jurnal Nomosleca, 2024)
GoJek is an example of an innovative technology-based company that has a bigimpact on humans in meeting their needs. One of the services provided by this application is Go-Food, which is an online delivery service on the Gojek application which is used by customers to find and order food. and working with more than 125,000 restaurants in various cities in Indonesia. The purpose of this study is to find out or provide an overview of the impact of Go-Food promos on the Gojek application on consumer behavior for users of the application, especially among UM students. This study used a qualitative research method. The data collection method used interview techniques. The results of this study indicate that the promos available on Go-Food services have a minimum purchase, this triggers the emergence of consumptive behavior, consumptive behavior occurs due to a promo on Go-Food services and causes food waste. Food waste certainly doesn't happen suddenly, but there are several influencing factors such as consumptive behavior.